Internal and External Egg Qualities of Layers Fed Two Proprietary Feeds Interchangeably - AO, Onabajo; HA, Awojobi; ES, Apata (Animal Review, 2022)
Four hundred and eighty, 53 weeks old Isa Brown layers were used for the 8 weeks feeding trial to determine the internal and external egg qualities of layers fed two proprietary feeds (designated Top feed (TF) and Animal Care feed (AC)) in five dynamics and two feeding frequencies. The birds were randomly allocated in a 5 x 2 factorial arrangement to five feeding dynamics (D1 TF only; D2 AC feed only; D3 weekly alternation of TF & AC; D4 Alternation of TF & AC every two weeks; D5 Monthly alternation of TF & AC) and two feeding frequencies (Twice & Thrice daily). Data were collected on external and internal egg qualities and analyzed using Analysis of variance (ANOVA). The results showed that both feeding dynamics and feeding frequencies significantly (p<0.05, R2=0.4) contributed to egg length as single factor. However, egg shape index (p=0.002), % yolk (0.00), yolk weight (p=0.004), egg moisture (0.003), egg fat (0.001) and egg carbohydrate (0.001) were influenced by interaction effect of feeding dynamics and feeding frequency. From the findings of this study, alternating brands of feed in the short term (weekly) and feeding laying birds twice daily is recommended.